Physicochemical properties of ice cream mixes - Mleko, Stanislaw; Sapiga, Victoria; Polishchuk, Galyna; Tomczynska-Mleko, Marta; Terpiłowski, Konrad; Pérez-Huertas, Salvador (My University, 2023)
The purpose of the work was to study the functional and technological properties of natural ingredients in low-calorie ice cream as potential structure stabilizers and fat substitutes. Ice cream mixes with β- glucans from oats and yeast, with fermented and non-fermented pectin-containing beet purée were studied. The viscosity of the mixes was measured on an ultrasonic viscometer Unipan type 505, viscoelastic properties on a Kinexus lab+ device, surface tension on a KSV Sigma 700 tensiometer, water activity on an AWMD-10 device.
Keywords: ice cream; viscosity; rheology; морозиво; в'язкість; реологія; кафедра технології молока і молочних продуктів